2016
DOI: 10.1186/s13068-016-0676-x
|View full text |Cite
|
Sign up to set email alerts
|

Biorefinery cascade processing for creating added value on tomato industrial by-products from Tunisia

Abstract: BackgroundIn today’s consumer perception of industrial processes and food production, aspects like food quality, human health, environmental safety, and energy security have become the keywords. Therefore, much effort has been extended toward adding value to biowastes of agri-food industries through biorefinery processing approaches. This study focused, for the first time, on the valorization of tomato by-products of a Tunisian industry for the recovery of value-added compounds using biorefinery cascade proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…for the S exh and A exh respectively that corresponded to an average biodegradability increase of 64%. This result agreed with previous works that described an increase of fibre availability measured as sugars-free fraction (Kehili et al, 2016).Ionic liquid (IL) was already able to improve fibre biodegradability, however exhaust biomass was IL polluted and unusable as AD feedstock (Allison and Simmons, 2017). On the contrary, SFE-CO 2 gave exhaust biomass solvent-free, dried and sterilised, characteristics that improved TP exh reusability respect to the TP raw .…”
Section: Tp-sfe-co 2 Effect On the Fibre Composition And Biodegradabisupporting
confidence: 91%
See 2 more Smart Citations
“…for the S exh and A exh respectively that corresponded to an average biodegradability increase of 64%. This result agreed with previous works that described an increase of fibre availability measured as sugars-free fraction (Kehili et al, 2016).Ionic liquid (IL) was already able to improve fibre biodegradability, however exhaust biomass was IL polluted and unusable as AD feedstock (Allison and Simmons, 2017). On the contrary, SFE-CO 2 gave exhaust biomass solvent-free, dried and sterilised, characteristics that improved TP exh reusability respect to the TP raw .…”
Section: Tp-sfe-co 2 Effect On the Fibre Composition And Biodegradabisupporting
confidence: 91%
“…The extracts' antioxidant power depended on the TP rawIM content and on the extraction process that was carried out at high temperature to increase lyc recovery while destroying other thermolabile molecules, a process which might have decreased the antioxidant properties (Shi and Maguer, 2000;Vàgi et al, 2007;Egydio et al, 2010;Liu et al, 2011;Kehili et al, 2016;Mutsokoti et al, 2017).…”
Section: Tp-sfe-co 2 Effect On Extract Physical Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste of tomatoes can be used for bulk juices and natural dyes. Results indicated that tomato byproducts are not only a green source of lycopene-rich oleoresin and tomato seed oil (TSO) and of protein with good nutritional quality but also a source of lignocellulosic matter with potential for bioethanol production [26].…”
Section: Waste Stream Usementioning
confidence: 99%
“…Thus Egypt has huge amounts of tomato crop residues and agroindustrial wastes; leaves, stems, pomace (skin, seeds and pulps). Tomato Agroindustrial Wastes (TAW) could be used for producing different valuable products, such as carotenoids, proteins and it can be used also as a potential feedstock for ethanol production not only because of their low cost and high availability but also because of their considerable amount of sugars and low content of lignin [5].…”
Section: Introductionmentioning
confidence: 99%